Moving beyond classic readability formulas: new methods and new models. (13th September 2019) - Crossley, Scott A.; Skalicky, Stephen; Dascalu, Mihai
Abstract : Background: Advances in natural language processing (NLP) and computational linguistics have facilitated major improvements on traditional readability formulas that aim at predicting the overall difficulty of a text. Recent studies have identified several types of linguistic features that are theoretically motivated and predictive of human judgments of text readability, which outperform predictions made by traditional readability formulas, such as Flesch–Kincaid. The purpose of this study is to develop new readability models using advanced NLP tools to measure both text comprehension and reading speed. Methods: This study used crowdsourcing techniques to collect human judgments of text comprehension and reading speed across a diverse variety of topic domains (science, technology and history). Linguistic features taken from state‐of‐the‐art NLP tools were used to develop models explaining human judgments of text comprehension and reading speed. The accuracy of these models was then compared with classic readability formulas. Results: The results indicated that models employing linguistic features more theoretically related to text comprehension and reading speed outperform classic readability models. Conclusions: This study developed new readability formulas based on advanced NLP tools for both text comprehension and reading speed. These formulas, based on linguistic features that better represent theoretical and behavioural accounts of the reading process, significantly outperformed classic readability formulas.